Research on the impact of traditional Chinese medicine registration innovation-oriented policies and enterprises performance: an empirical analysis based on listed enterprises in China - Lv, Junfeng; Lu, Kaidi; Xie, Ming; Sun, Wanping; Liu, Yiming (Frontiers in Public Health, 2025)
ObjectiveThe performance of traditional Chinese medicine (TCM) enterprises is affected by various factors, among which the impact of TCM Registration Innovation-Oriented policies (TCMRIPs) may be involved. TCMRIPs, in turn, improve enterprises performance by influencing TCM enterprises’ R&D investment. This aim of this study is to explore the impact of TCMRIPs on the performance of TCM enterprises, and the mediating role of R&D investment in this process.MethodsThis study constructs an unbalanced panel fixed model to empirically analyze the impact of TCMRIPs on enterprise performance and their heterogeneous characteristics, and examines the mediating effect of R&D investment.ResultsThe results show that the performance of TCM listed enterprises in China has a significant positive correlation with TCMRIPs. TCMRIPs play a positive role in TCM listed enterprises performance.ConclusionThis study also indicates that R&D investment plays a mediating role in the effect of TCMRIPs on the performance of TCM listed enterprises in China, and the impact of policies on enterprise performance has a lag. The new version of the Drug Registration Administration Measures, the TCM registration classification, and the mechanisms they bring can promote the improvement of enterprise performance more effectively than the previous policies and mechanisms.